A Resource-Based Approach to the Multi-Business Firm: Empirical Analysis of Portfolio Inter-Relationships and Corporate Financial Performance - ROBINS, James Arthur (Institutional Knowledge at Singapore Management University, 1993)
The resource-based view of the firm has provided important new insights into corporate strategy (Barney, 1991; Peteraf, 193); however, there has been only limited empirical research linked to the theory (e.g., Farjoun, 1994). Although a great deal of work has been done on corporate diversification, the measures and data typically have a weak connection to resource-based theory. Empirical research on resource-based corporate strategy has been particularly difficult because key concepts such as tacit knowledge or capabilities resist direct measurement. This study is an effort to narrow the gap between theory and empirical research on the multibusiness firm. It develops a resource-based approach to modeling interrelationships among businesses and applies it to the analysis of corporate economic performance. This approach proves to be significant in explaining the financial performance of large manufacturing firms, and it promises to be an important source of insight into corporate strategy.